EFEKTIVITAS TUTOR TEMAN SEBAYA DALAM PENCAPAIAN PEMAHAMAN SISWA PADA MATA PELAJARAN GAMBAR TEKNIK MANUFAKTUR - Muhammad Yusri Dzal Yahya; Syahrial Shaddiq; Arya Yusuf; Siti Nursipa Wulida (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2025)
Individual differences in understanding are crucial in education, requiring teachers to tailor learning activities to meet students' needs. This study conducted as a quasi-experiment, involved 72 students from two classes (XI TM A and XI TM B) at SMK Negeri 1 Magelang during the 2023/2024 academic year. The research utilized a post-test only control group design to assess the effectiveness of peer tutoring. The experimental group had an average score of 96.90, while the control group averaged 94.29. The experimental group's scores ranged from 90.5 to 100 and the control group's scores ranged from 77.5 to 97. Statistical analysis using levene's test showed homogeneous data (Pvalue = 0.189 > α = 0.05). The t-test indicated a significant effect of peer tutoring on students' understanding of technical drawing (Tcount = 4.003 > Ttable = 2.000). The study concluded that peer tutoring significantly improves student performance in the manufacturing engineering drawing subject, recommending further research on its effectiveness in other subjects and educational levels.